Simple high‐performance liquid chromatography method for formaldehyde determination in human tissue through derivatization with 2, 4‐dinitrophenylhydrazine. Issue 15 (5th July 2016) - Yilmaz, Bilal; Asci, Ali; Kucukoglu, Kaan; Albayrak, Mevlut
Abstract : A simple high‐performance liquid chromatography method has been developed for the determination of formaldehyde in human tissue. FA Formaldehyde was derivatized with 2, 4‐dinitrophenylhydrazine. It was extracted from human tissue with ethyl acetate by liquid–liquid extraction and analyzed by high‐performance liquid chromatography. The calibration curve was linear in the concentration range of 5.0–200 μg/mL. Intra‐ and interday precision values for formaldehyde in tissue were <6.9%, and accuracy (relative error) was better than 6.5%. The extraction recoveries of formaldehyde from human tissue were between 88 and 98%. The limits of detection and quantification of formaldehyde were 1.5 and 5.0 μg/mL, respectively. Also, this assay was applied to liver samples taken from a biopsy material.